Energy-saving privacy data secure aggregation method - Yong-hao GU; Da GUO; Jiu-chuan LIN (Tongxin xuebao)
For the Internet of things(IoT) secure data aggregation issues,data privacy-preserving and limited computation ability and energy of nodes should be tradeoff.Based on analyzing the pros-and-cons of current works,a low energy-consuming secure data aggregation method (LCSDA) was proposed.This method uses shortest path principle to choose neighbor nodes and generates the data aggregation paths in the cluster based on prim minimum spanning tree algorithm.Simulation results show that this method could effectively cut down energy consumption and reduce the probability of cluster head node being captured,in the same time preserving data privacy.